Liver Fat Content Is Associated with Elevated Serum Uric Acid in the Chinese Middle-Aged and Elderly Populations: Shanghai Changfeng Study - Lin, Huandong (PLoS One, 2015)
BACKGROUND AND AIMS: Although many studies have indicated a relationship between nonalcoholic fatty liver disease (NAFLD) and hyperuricemia, a few studies specifically examining the effects of the severity of liver fat content (LFC) on serum uric acid (SUA) and the presence of hyperuricemia because of the limitation of the examination methods for NAFLD. In this study, we investigate the relationship between the NAFLD and SUA levels in the Chinese population using standardized quantitative ultrasound. METHODS: A community-based study was conducted from May 2010 to December 2012. A total of 4,305 people aged 45 years and above without excessive drinking were enrolled. A standard interview and anthropometric and laboratory blood parameters were collected for each person. The standardized ultrasound hepatic/renal ratio and hepatic attenuation rate was used to quantify LFC. RESULTS: The prevalence of NAFLD and hyperuricemia was 33.1% and 17.1%, respectively. A total of 23.5% of the NAFLD subjects had hyperuricemia, and their SUA was higher than that of non-NAFLD subjects (327.2±76.8 vs 301.9±77.4 μmol/L, P<0.001). The LFC was positively correlated with SUA (r = 0.130, P<0.001) and an independent factor for SUA (standardized β = 0.054, P<0.001). The OR for the presence of hypreuricemia was 1.175 (95% CI 1.048–1.318; P<0.001) with a 1 SD increase in the log LFC. LFC greater than 10% was related to elevated SUA and an increased presence of hyperuricemia. CONCLUSIONS: LFC accumulation was associated with an increase in the prevalence of hyperuricemia and elevated SUA in our community-based population. LFC greater than 10% is related to the risk for hyperuricemia.